The Struggle of Afro American Women as Revealed in Walker’s The Color Purple - Tini Mogea (Student Scientific Creativity Journal, 2023)
This research intends to find out the struggle of Afro-American women against discrimination in Alice Walker’s The Color Purple. This research is qualitative, which means that the data are in the form of words; thus, the data came from the novel and other books that are relevant to this research. A mimetic approach is used in data analysis to unearth the literary work as an imitation or reflection of aspects of human life, such as sociological, historical, or psychological background that is related to the topic. The result shows that the Afro-American women that are pictured in Celie’s life should struggle against both white and black discrimination. The whites did not accept the existence of the blacks and treated them cruelly through violence, rape, and murder. On the other side, the black man oppressed the Afro-American woman through sex abuse, physical abuse, and economic depression. The black women were living under the protection of men. However, their protection is no better than dominance and subservience. Even though Celie was treated abruptly and disrespectfully by her father and her husband, she could face it bravely, increasing her knowledge and insights, achieving financial success, and being happy in her life. Therefore, she achieves self-esteem, self-acceptance, economic independence, and, above all, freedom for the whole of her life. This is the realization of African American women's desire to gain recognition as individuals who deserve fair and equal treatment.